UPAYA PELESTARIAN MANGROVE MELALAUI PERBAIKAN TEKNIK PEMBIBITAN DI DESA JEROWARU, KECAMATAN JEROWARU, KABUPATEN LOMBOK TIMUR - Ibadur Rahman; Nurliah Buhari; Ayu Adhita Damayanti; Edwin Jefri; Wiwid Andriyani Lestariningsih (Jurnal Abdi Insani, 2022)
Today's mangrove ecosystem is increasingly under pressure, mainly due to the conversion of mangrove land into aquaculture, tourism, and industrial areas. At the same time, the mangrove ecosystem has a very vital role in life. Efforts have been made to slow down the degradation rate of the mangrove ecosystem, including by replanting activities (reforestation). Mangrove planting activities are often constrained by the lack of healthy seeds or a mismatch between the seeds and the planting environment. It causes the planted mangrove seedlings not to be able to grow appropriately and even die. This community service activity aims to educate and assist the community in Poton Bako Hamlet, Jerowaru Village, Jerowaru District, East Lombok Regency regarding mangrove nursery techniques, especially R. mucronata and S. alba species, properly and correctly. The method used is using booklet media and direct practical assistance. Moreover, the community listens and practices what has been conveyed regarding nursery procedures. The results of this activity received high enthusiasm from the community, and the community felt its usefulness. This mentoring activity requires follow-up in the form of continuous control and assistance so that future nursery programs carried out independently by the community can continue and run optimally. In the future, it is hoped that the community's independence to carry out mangrove nurseries can run well. Thus what has been obtained by the community can be transmitted to others so that mangrove conservation is maintained.